Spectrophotometric Determination of Cobalt with m-(Mercaptoacetamido) phenol. - Appadoo, Chandani; Bhagwat, V.W. (Asian Journal of Chemistry, 2010)
The reagent m-(mercaptoacetamido) phenol forms a purpule 1 : 2 complex with cobalt which is soluble in sodium hydroxide solution. The reagent has been used for the spectrophotometric estimation of cobalt. The complex has a maximum at 480 nm with molar absorptivity 1.04 x 104 1 mol–1 cm–1. The effect of interfering ions has been studied and the method was applied to cobalt(II) determination in vitamin preparations.